Theoretical Models and Processes of Reading 2013
DOI: 10.1598/0710.44
|View full text |Cite
|
Sign up to set email alerts
|

Imagined Readers and Hospitable Texts: Global Youths Connect Online

Abstract: n our radically interconnected world, with its global and digital flows of people, capital, and information, texts can rapidly circulate far and wide, across cultural, geographic, and linguistic borders. These texts require of those who would communicate effectively the flexible capacity to make meaning across an increasingly complex range of textual forms that integrate multiple semiotic modalities (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…Each of these replies expanded thematically from the previous Zeegas by using selected components, such as the images, music, and sequencing patterns. Across the week, remixing as reply functioned in similar ways to the "reciprocity stance" witnessed by Hull, Stornaiuolo and Sterponi [54] in their studies of youths' reading and writing orientations in an international social network. With a reciprocity stance, authors assume collaborative relationships of shared texts and abilities, and position compositions as extensions of ongoing conversations, or connections to common understandings across people.…”
Section: Bursting: Velocities Of Production and Interactivitymentioning
confidence: 86%
“…Each of these replies expanded thematically from the previous Zeegas by using selected components, such as the images, music, and sequencing patterns. Across the week, remixing as reply functioned in similar ways to the "reciprocity stance" witnessed by Hull, Stornaiuolo and Sterponi [54] in their studies of youths' reading and writing orientations in an international social network. With a reciprocity stance, authors assume collaborative relationships of shared texts and abilities, and position compositions as extensions of ongoing conversations, or connections to common understandings across people.…”
Section: Bursting: Velocities Of Production and Interactivitymentioning
confidence: 86%
“…We analyzed these participation and multimodal records as well as the ethnographic data by means of the qualitative data analysis software Atlas.ti, engaging in multiple rounds of open‐ended and thematic coding (Saldaña, ; Strauss & Corbin, ) as we endeavored to understand how our participants traversed multiple semiotic systems and engaged with interlocutors distant from themselves. As we detail below, we identified several significant patterns in how composers took their audiences into account, building on our efforts to identify audience‐sensitive textual strategies in creating hospitable texts (Hull et al., ). Specifically, we found that authors took up three primary rhetorical stances (cf.…”
Section: Methodsmentioning
confidence: 99%
“…In Emilio's video and in his subsequent blog, he paints himself as an open and inviting interlocutor who would be willing to hear responses to his work should anyone choose to provide them. We have argued elsewhere that this stance of openness is a fundamentally hospitable disposition, one crucial for authoring in networked contexts in the 21st century (Hull et al., ). We also suggest that it is a fundamental element in negotiating proper distance, part of locating oneself as an ethical participant in relation to others.…”
Section: Negotiating Proper Distance: Creating Spaces For Understandingmentioning
confidence: 99%
See 2 more Smart Citations